HPLC Method for the Estimation of Nicorandil in Pharmaceutical Dosage Forms - Krishnaiah, Y.S.R.; Rama, B.; Raju, V.; Jayaram, B.; Bhaskar, P.; Murali Mohan Rao, P. (Asian Journal of Chemistry, 2010)
A reverse phase high pressure liquid chromatographic method (HPLC) has been developed for the estimation of nicorandil in its tablet dosage forms using RP-C18 column. The mobile phase (acetonitrile and 0.02 M potassium dihydrogen orthophosphate)-was pumped at a flow rate of 0.8 mL/min in the ratio 40 : 60, and the eluents were monitored at 254 nm. The intra- and inter-day variation was found to be less than 2.5% showing high precision of the assay method. The mean recovery of the drug from the Solutions containing 4 or 6 μg/mL was 99.83 ± 0.2% indicating high accuracy of the proposed HPLC method. Due to its simplicity, rapidness, high precision and accuracy, the proposed HPLC method may be used for determining nicorandil in bulk drug samples or in tablet dosage forms.